1982
DOI: 10.1007/bf01965941
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, insect sterilizing and ovicidal activity of some oxo-vanadium(IV) and oxo-vanadium(V) complexes

Abstract: Twenty-three newly synthesized mixed-ligand complexes of oxo-vanadium(IV) and oxo-vanadium(V) were studied for antimicrobial activity. Eight of these complexes were found to have microbicidal properties. The complexes [NH4][VO(gl)2]H2O (gl-H2 = glycolic acid) and [VO(ACOAP)(acac-H)]H20 (ACOAP-H2=Schiff base of acetylacetone and orthoaminophenol, acac-H=acetyl-acetone) show broad bactericidal spectra, while the complexes [VO(ACSAM)2]OH (ACSAM-H = Schiff base of acetylacetone and sulphanilamide) and [VO(CSSAM-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Vanadium is widely distributed in the biosphere and its essential role has been recognized in both plants and animals. e oxovanadium(IV) cation has been found to inhibit the plasma membrane ATPase of Neurospora crassa and Saccharomyces cerevisiae, the proton translocating ATPase of Mycobacterium phlei and Ca ++ -ATPase of red cell membranes [1][2][3]. It has been observed that the free vanadyl ion is oxidized to vanadate within a few minutes in aqueous solution exposed to air at neutral pH [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium is widely distributed in the biosphere and its essential role has been recognized in both plants and animals. e oxovanadium(IV) cation has been found to inhibit the plasma membrane ATPase of Neurospora crassa and Saccharomyces cerevisiae, the proton translocating ATPase of Mycobacterium phlei and Ca ++ -ATPase of red cell membranes [1][2][3]. It has been observed that the free vanadyl ion is oxidized to vanadate within a few minutes in aqueous solution exposed to air at neutral pH [4][5][6].…”
Section: Introductionmentioning
confidence: 99%